Growing Gardenias in Florida - Joan Bradshaw; Sydney Park Brown (EDIS)
Revised! Circular 1098, a 7-page illustrated fact sheet by Joan Bradshaw and Sydney Park Brown, provides guidelines for growing this evergreen shrub known for the sweet scent of its wax-like blossoms — site selection, planting, maintenance practices, pests and other problems, cultivars, and propagation. Includes references. Published by the UF Department of Environmental Horticulture, May 2009.